Customizing supercontinuum generation via on-chip adaptive temporal pulse-splitting - Benjamin Wetzel (Nature Portfolio, 2018)
Controlling complex properties of optical systems, like the output of nonlinear light sources, is increasingly important for applications. Here, Wetzel et al. use an actively-controlled photonic chip to prepare patterns of femtosecond laser pulses used for tailoring supercontinuum generation.